2020
DOI: 10.1002/pbc.28565
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination in pediatric cancer survivors: Vaccination rates, immune status, and knowledge regarding compliance

Abstract: Background Vaccination recommendations for childhood cancer survivors are ambiguous. Limited data exist on vaccination rates and patient/caregiver knowledge of vaccination postchemotherapy. Procedure A single‐institution study of childhood cancer survivors treated from 1996 to 2018. Study included a retrospective chart review assessing patient's vaccination status, survey of patient's/caregiver's knowledge/beliefs regarding vaccination postchemotherapy, and assessment of immunoglobulin titers. Results A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…We found that the older the child, the lower the vaccination rate; the earlier the tumor diagnosis, the lower the vaccination rate; the more severe the disease classification of children, the lower the coverage rate of the second dose of MPSV-AC vaccine, and they are consistent with the current survey results ( 37 , 38 ). The possible reasons are as follows: Firstly, it is related to the limitation of vaccination age.…”
Section: Discussionsupporting
confidence: 89%
“…We found that the older the child, the lower the vaccination rate; the earlier the tumor diagnosis, the lower the vaccination rate; the more severe the disease classification of children, the lower the coverage rate of the second dose of MPSV-AC vaccine, and they are consistent with the current survey results ( 37 , 38 ). The possible reasons are as follows: Firstly, it is related to the limitation of vaccination age.…”
Section: Discussionsupporting
confidence: 89%
“…The HPV vaccine is indicated for immunocompromised individuals and the Children's Oncology Group (COG) recommends resuming vaccines 3–6 months post‐therapy and 6–12 months for live vaccines, suggesting that education for providers and caregivers may be necessary for increasing HPV vaccination uptake for survivors 27,33 33 4 …”
Section: Discussionmentioning
confidence: 99%
“…Studies [214][215][216][217][218][219][220] have shown that the vaccine can activate the body's immune system, promote the expression and recognition of tumor-associated antigens, and trigger a specific immune response against tumor cells. Through mannose modification, the vaccine can be more effectively taken up by antigen-presenting cells and improve its efficiency of antigen delivery in the lymph nodes, further activating immune cells such as dendritic cells and T cells and enhancing the potential of the immune response [221].…”
Section: Enhancement Of Tumor Immune Response and Establishment Of Im...mentioning
confidence: 99%